The effects of reading for pleasure on efl students’ reading comprehension - Santos Mera, Lisbeth (2022)
This research addresses the development of reading skills in English as a foreign language by strengthening motivational aspects in students with school lag. Reading is the main instrument in the teaching-learning process because it is involved in the cognitive progress of students. The importance of developing reading skills in English is also related to the mother tongue so that it is a complement for comprehensive improvement. It was concluded that the development of reading skills in the population studied, in this case, students of second and third years of baccalaureate at Simon Bolivar high school in Portoviejo City, is low and there are few methodologies applied by teachers that do not allow reaching the required reading comprehension and through a proposal it is intended to help students acquire new vocabularies and short structures in English, so they will become familiar with reading and then writing, they will also learn to work by playing in groups, and to invent small stories with their own effort. To have significant learning, the teacher must use the proposed planning; structure it in advance and consider the aspects that contribute to the increase of linguistic intelligen